SARS-CoV-2 and Human Immunodeficiency Virus: Pathogen Pincer Attack - Evans, Nicholas (HIV AIDS (Auckl), 2021)
Paramount efforts worldwide are seeking to increase understanding of the basic virology of SARS-CoV-2, characterize the spectrum of complications associated with COVID-19, and develop vaccines that can protect from new and recurrent infections with SARS-CoV-2. While we continue learning about this new virus, it is clear that 1) the virus is spread via the respiratory route, primarily by droplets and contact with contaminated surfaces and fomites, as well as by aerosol formation during invasive respiratory procedures; 2) the airborne route is still controversial; and 3) that those infected can spread the virus without necessarily developing COVID-19 (ie, asymptomatic). With the number of SARS-CoV-2 infections increasing globally, the possibility of co-infections and/or co-morbidities is becoming more concerning. Co-infection with Human Immunodeficiency Virus (HIV) is one such example of polyparasitism of interest. This military-themed comparative review of SARS-CoV-2 and HIV details their virology and describes them figuratively as separate enemy armies. HIV, an old enemy dug into trenches in individuals already infected, and SARS-CoV-2 the new army, attempting to attack and capture territories, tissues and organs, in order to provide resources for their expansion. This analogy serves to aid in discussion of three main areas of focus and draw attention to how these viruses may cooperate to gain the upper hand in securing a host. Here we compare their target, the key receptors found on those tissues, viral lifecycles and tactics for immune response surveillance. The last focus is on the immune response to infection, addressing similarities in cytokines released. While the majority of HIV cases can be successfully managed with antiretroviral therapy nowadays, treatments for SARS-CoV-2 are still undergoing research given the novelty of this army.